PATIENT SAFETY ISSUES: THE ROLE OF ORGANIZATIONAL BEHAVIORAL APPROACH (OBA) IN ADDRESSING ISSUES RELATED TO MEDICAL ERROR AND SAFETY CULTURE - Fatmawati Fatmawati; Muhammad Taufik (Psikoislamedia : Jurnal Psikologi, 2016)
During these recent years, patient safety has become a prominent issue in the medical atmosphere and appeared to be the main target for improvement (Leroy et al., 2012). As one of the disciplines in health sciences, psychology might play an important role in addressing the problems occurred in patient safety. There are broad aspects where psychology may contribute (Nash, McKay, Vogel, & Masters, 2012), but the involvement of psychology in changing the safety within health care setting has been underestimated and its role has been partially described (Ã˜vretveit, 2009).Therefore, this paper is proposed in order to demonstrate one of the behavioral theories in psychology, named the Organizational Behavioral Approach (OBA) to give a wider understanding on how psychologist may contribute to address the issues in patient safety, especially the problems related to medical error and safety culture.